The need achievement orientation of Catholic and Protestant Mexican-Americans - Bronson, Louise; Meadow, Arnold (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Need-achievement orientations of fifty-four Protestant and fifty-four Catholic Mexican-American subjects of similar levels of acculturation and socio-economic background are here reported. It was hypothesized that values relevant to the “Protestant Ethic” would be reflected by Protestant subjects. One instrument, evaluating basic achievement motivation, reflected an equal drive in both groups but a second instrument reflecting values and attitudes showed the Protestants to have achievement goals more related to an activistic-individualistic-future orientation. It is suggested that certain elements of the Protestant religion such as stewardship, individual responsibility, asceticism and self-discipline are responsible for the attitude differences expressed by Protestant subjects.